Determinant Factors of Compliance Antiretroviral Consumption in People Living with HIV AIDS (PLWHA) - Mutmainah, Mutmainah; Supriyadi, Supriyadi; Herawati, Fondha; Mufida, Umdah (Poltekkes Kemenkes Surakarta, 2023)
Background: The Human Immunodeficiency/Acquired Immune Deficiency Syndrome (HIV AIDS) is one of the most deadly diseases. Obedience to drink ARV drugs becomes a deciding factor in the quality of life of PLWHA patients. Determinant factors of compliance not taking ARVs yet found in a certain way. Objectives from the study This is to describe determinant factors of compliance with ARV consumption for people living with HIV AIDS (PLWHA) at home in Sick Surakarta Central General. Methods: Type study This is a descriptive-analytic approach designed to be cross-sectional. The population is all HIV AIDS patients undergoing ARV therapy maintained at Jalan RSUP Surakarta, with as many as 49 patients. Data collection techniques use total sampling. Data collection is done using a questionnaire for ART compliance (Life Windows Information-Motivation-Behaviorak Skill). Data analysis techniques include univariate and bivariate analysis with the Chi-Square test. Results: Research results show (1) Chi-Square test result information (p = 3.027). (2) Results of the Chi-Square test of motivation (p = 0.776) (3) Chi-Square test results: skills and behavior (p = 2.982). No There is a significant influence between information, motivation, and skills associated with obedience to drug ARVs. (1) Odd Ratio Test Results Information (p = 0.244), Odd Ratio Test Results Motivation (p = 0.420), Nagelkerke's R Square (p = 0.185), or 18.5%. Conclusion: Support family is very influential in influencing obedience to drug ARVs, so officer health must involve families and always give support to patients who receive ARV therapy.